+0  
 
+1
44
8
avatar+12 

Furthermore, how/why do powers of non-integers work? For example, why would (-1)^1.5 be -i?

Epic8009  Nov 10, 2017
Sort: 

8+0 Answers

 #1
avatar+333 
0

(-1) ^ 1.5 is 1.

 

2^0.5 is basically just multiplying 2 0.5 times, which is square root. 

supermanaccz  Nov 10, 2017
 #2
avatar+12 
0

I'm not sure I understand. 2*0.5 is NOT sqrt(2).

Epic8009  Nov 10, 2017
 #4
avatar+91047 
0

2^0.5   IS   sqrt(2)

Melody  Nov 11, 2017
 #3
avatar+91047 
+2

(-1)^1.5 

 

\((-1)^{1.5}\\ = (-1)^{\frac{3}{2}}\\ \text{I can look at this in 2 different ways so lets see what happens.}\\ = [(-1)^3]^{\frac{1}{2}}\qquad or \qquad [(-1)^\frac{1}{2}]^{3}\\ = [-1]^{\frac{1}{2}}\qquad or \qquad [\sqrt{-1}]^{3}\\ =\sqrt{-1}\qquad or \qquad [i]^{3}\\ =\pm i \qquad \qquad or \qquad -i\\ \)

 

The only common answer is -i so I guess that is the only correct answer.

 

Maybe another mathematician would like to comment here......

Melody  Nov 11, 2017
 #5
avatar+12 
0

How did you get from \(\left(-1\right)^{\frac{1}{2}}\)to \(\sqrt{-1}\)?

Epic8009  Nov 11, 2017
edited by Epic8009  Nov 11, 2017
 #6
avatar+26329 
+1

This is what WolframAlpha says Melody:

 

Alan  Nov 11, 2017
 #7
avatar+1375 
+1

\((-1)^{\frac{1}{2}}\Rightarrow\sqrt{-1}\)  is a law of fractional exponents. In general terms, \(x^{\frac{a}{b}}=\sqrt[b]{x^a}=\left(\sqrt[b]{x}\right)^a\)

 

Why is this the case? Well, I can attempt to explain it to you.

 

The law of exponents explains how to handle multiplication of exponents with identical bases. 

 

\(x^3*x^2=x^{3+2}=x^5\)

 

Let's try another example but with fractional exponents.

 

\(3^{\frac{1}{2}}*3^{\frac{1}{2}}=3^{\frac{1}{2}+\frac{1}{2}}=3^1=3\)

 

In this example here, \(3^{\frac{1}{2}}\) is a number that when multiplied by itself yields 3. That sounds like the definition of the square root, doesn't it? Therefore, \(3^{\frac{1}{2}}=\sqrt{3}\). One can also expound upon this.

 

\(3^{\frac{1}{3}}*3^{\frac{1}{3}}*3^{\frac{1}{3}}=3^{{\frac{1}{3}}+{\frac{1}{3}}+{\frac{1}{3}}}=3^1=3\)
\(3^{\frac{1}{4}}*3^{\frac{1}{4}}*3^{\frac{1}{4}}*3^{\frac{1}{4}}=3^{\frac{1}{4}+\frac{1}{4}+\frac{1}{4}+\frac{1}{4}}=3^1=3\)
\(3^{\frac{1}{5}}*3^{\frac{1}{5}}*3^{\frac{1}{5}}*3^{\frac{1}{5}}*3^{\frac{1}{5}}=3^{\frac{1}{5}+\frac{1}{5}+\frac{1}{5}+\frac{1}{5}+\frac{1}{5}}=3^1=3\)
\(3^{\frac{1}{x}}*3^{\frac{1}{x}}*3^{\frac{1}{x}}*...*3^{\frac{1}{x}}*3^{\frac{1}{x}}=3^{\frac{1}{x}+\frac{1}{x}+\frac{1}{x}+...+\frac{1}{x}+\frac{1}{x}}=3^1=3\)

 

The pattern continues. \(3^{\frac{1}{3}}\) is a number that when multiplied by itself 3 times yields 3. This is the definition of the cubic root. Then, as you can see, I made a generalization. \(3^{\frac{1}{x}}\), when multiplied x times, yields 3. 

TheXSquaredFactor  Nov 11, 2017
 #8
avatar+12 
0

Thank you!

Epic8009  Nov 11, 2017

3 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details